2012
DOI: 10.1007/s00394-012-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

The renoprotective effect of l-carnitine in hypertensive rats is mediated by modulation of oxidative stress-related gene expression

Abstract: Our results might support the use of LC to prevent hypertension-induced renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 51 publications
6
20
0
1
Order By: Relevance
“…The results of the present study, revealed that L-carnitine caused a significant decrease in testicular NF-κB expression and TNF-α and NO production. These effects are in line with previous studies which reported that L-carnitine can block the activation of NF-κB signaling pathway (Arafa, 2008;Zambrano et al, 2013). In addition, Ahmed et al (2014) stated that, Lcarnitine exhibited a powerful down-regulation of mRNA expression of TNF-α and this could be explained in part by its antioxidant activities (Thangasamy et al, 2009) and also by its glucocorticoid-like effect on the expression of pro-inflammatory cytokines (Schetter et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study, revealed that L-carnitine caused a significant decrease in testicular NF-κB expression and TNF-α and NO production. These effects are in line with previous studies which reported that L-carnitine can block the activation of NF-κB signaling pathway (Arafa, 2008;Zambrano et al, 2013). In addition, Ahmed et al (2014) stated that, Lcarnitine exhibited a powerful down-regulation of mRNA expression of TNF-α and this could be explained in part by its antioxidant activities (Thangasamy et al, 2009) and also by its glucocorticoid-like effect on the expression of pro-inflammatory cytokines (Schetter et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The kidney plays an important role in the metabolism of LC (it reabsorbs more than 95% of filtered LC, apart from participating in LC synthesis). LC prevented hypertension-associated renal function damage by reversion of the alterations induced in the activities, protein, and gene expressions of the antioxidant enzymes GPx, GR, and SOD [162]. It also produced up-regulation of eNOS (the enzyme responsible for nitric oxide production), and down-regulation of the renin–angiotensin system (RAS) components and NADPH oxidase subunits NOX2 and NOX4 [163].…”
Section: Cylindrospermopsinmentioning
confidence: 99%
“…LC seemed to improve the oxidative stress response through a specific modulation of nuclear transcription factors kappa B (NF-κB), Nrf2, and peroxisome proliferator-activated receptor alpha (PPARα). Therefore, inhibition of NADPH oxidase led to less production of superoxide anions, which may increase the expression of Nrf2 and PPARα and decrease that of NF-κB, thus enhancing the antioxidant defense systems [162]. In this regard, LC anti-inflammatory properties have also been reported by inhibition of the NF-κB pathway by suppression of ROS formation [164,165].…”
Section: Cylindrospermopsinmentioning
confidence: 99%
“…Advanced glycation-end products (AGEs) are a group of heterogeneous compounds formed through nonenzymatic oxidative and nonoxidative reactions between proteins and reactive carbonyl compounds derived from carbohydrates and lipids (Peppa and Raptis, 2008). L-carnitine has also been shown to prevent oxidative injury in renal and cardiovascular disease (Zambrano et al, 2013). The antioxidant potential of L-carnitine has been demonstrated (G€ ulçin, 2006;Fatouros et al, 2010), as well as its neuroprotective effect (Ribas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant potential of L-carnitine has been demonstrated (G€ ulçin, 2006;Fatouros et al, 2010), as well as its neuroprotective effect (Ribas et al, 2014). L-carnitine has also been shown to prevent oxidative injury in renal and cardiovascular disease (Zambrano et al, 2013). Carnicor, a natural supplement of L-carnitine, is usually administered to most of the ESRD patients after each dialysis session to recover the amount lost during the dialysis process.…”
Section: Introductionmentioning
confidence: 99%